The role of impurities and degradation on the thermal conductivity of carbon fiber and amorphous carbon. (April 2022) - Konnik, Matthew T.; Panerai, Francesco; Stephani, Kelly A.
Graphical abstract: Abstract: Carbon microstructures evolve due to exposure to rapidly oxidizing environments. The evolution of these structures can fundamentally change intrinsic material properties and therefore performance. In this study, we use molecular dynamics to investigate the sensitivity of carbon fiber and amorphous carbon thermal conductivities to defects introduced as a consequence of these environmental factors. Pristine microstructures are first evaluated, followed by counterparts with the presence of impurities, oxygen, and etch pitting. Findings indicate diminished thermal transport capabilities of these materials for all defect types studied, and differences in conductivity of up to 50% as compared to pristine counterparts. We also conclude that etch pitting has a meaningful impact on these materials thermal response from the early stages of formation. Results found in this study advance our understanding of carbon fiber materials performance in extreme environments and serve as the basis for meso-scale simulations of effective material properties